The Effect Of Substitution Drill Technique On Students’ English Speaking Skill : Experimental Study at the fifth grade class of SDN 06 Makasar in East Jakarta - Mulyadi Mulyadi; Dery Saefudin; Ahmad Bakhtiar (English Language Education Department, Universitas Majalengka, 2024)
This research aims to investigate and validate the impact of the Substitution Drill technique on students' English speaking learning outcomes in fifth grade of SD 05 Makassar, East Jakarta. Substitution drill is a teaching method that falls under the Drill Method umbrella and is widely used in language instruction to train sounds and sentence patterns in a language. The activity entails repetitive practice to achieve permanent skills. In substitution drill, students are instructed to replace specific elements within a sentence or conversation. This study delves into the impact of substitution drill on students' English speaking proficiency. A total of 60 students were chosen as research samples using the total sampling method. Data for the study was gathered through interview tests. Subsequently, the data was subjected to quantitative analysis to ascertain the effect of the Substitution Drill technique on students' English speaking ability as part of the hypothesis test. Data analysis was performed using a t-test at a significance level (α) of 0.05. The findings of statistical tests reveal that the tobserved value is greater than the ttable, indicating a significant influence of the Substitution Drill technique on students' learning outcomes in English speaking skills.